Pengaruh Pengeluaran Konsumsi Rumah Tangga terhadap Produk Domestik Bruto Indonesia Tahun 2003-2022 - Siti Saadatu Daroen; M.Egitia Zaini; Nurul Nur Fadillah; Angelica Meilani Rika Dwi Kusuma; Anggita Ken Muktiari; Faldi Satrya Akbarullah; Dahri Dahri; Disya Ayu Rivtryana (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to analyze the influence of household consumption expenditure on Indonesia's Gross Domestic Product (GDP) in 2003-2022. The data used was taken from secondary data from the Central Statistics Agency (BPS) using simple linear regression as the analysis method. The research results show that there is a positive and significant relationship between household consumption expenditure and Indonesia's GDP. This means that an increase in household consumption expenditure will encourage Indonesia's GDP growth. The growth in household consumption shows that during the 2003-2022 period it can increase GDP, seen from every 1% increase in household consumption expenditure, it will increase Indonesia's GDP by 0.0901. The research results show that household consumption expenditure is one of the main components driving an increase in Indonesia's GDP. Thus, to encourage higher economic growth, efforts need. to be made to increase people's purchasing power and encourage productive household consumption.